2018
DOI: 10.1016/j.chom.2018.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Evolution of H7N9 Highly Pathogenic Viruses that Emerged in China in 2017

Abstract: Summary H7N9 low pathogenic influenza viruses emerged in China in 2013 and mutated to highly pathogenic strains in 2017, resulting in human infections and disease in chickens. To control spread, a bivalent H5/H7 inactivated vaccine was introduced in poultry in September 2017. To monitor virus evolution and vaccine efficacy, we collected 53,884 poultry samples across China from February 2017 to January 2018. We isolated 252 H7N9 low pathogenic viruses, 69 H7N9 highly pathogenic viruses, and one H7N2 highly path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
215
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(225 citation statements)
references
References 48 publications
(86 reference statements)
2
215
0
Order By: Relevance
“…Each genome segment of HE30‐1, with the exception of the NA (N3) segment, was compared at the nucleotide level with each segment of A/duck/Fujian/SE0195/2018 (FJ‐SE0195) (H7N2), which is a G9 genotype reassortant between an H7N9 HPAIV of the G8 genotype and an unknown duck virus and is highly pathogenic for domestic ducks (Shi et al, ), along with each segment of A/environment/Fujian/S10058/2017 (FJ‐S10058) (H7N9), A/duck/Japan/AQ‐HE29‐52/2017 (HE29‐52) (H7N9) and A/duck/Japan/AQ‐HE29‐22/2017 (HE29‐22) (H7N9). The latter two viruses were isolated from duck meat brought illegally from China to Japan, like HE30‐1 (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each genome segment of HE30‐1, with the exception of the NA (N3) segment, was compared at the nucleotide level with each segment of A/duck/Fujian/SE0195/2018 (FJ‐SE0195) (H7N2), which is a G9 genotype reassortant between an H7N9 HPAIV of the G8 genotype and an unknown duck virus and is highly pathogenic for domestic ducks (Shi et al, ), along with each segment of A/environment/Fujian/S10058/2017 (FJ‐S10058) (H7N9), A/duck/Japan/AQ‐HE29‐52/2017 (HE29‐52) (H7N9) and A/duck/Japan/AQ‐HE29‐22/2017 (HE29‐22) (H7N9). The latter two viruses were isolated from duck meat brought illegally from China to Japan, like HE30‐1 (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The zoonotic H7N9 AIVs could not replicate well in domestic ducks, and even if they were able to replicate, they were shed less frequently from ducks than from chickens (Hiono et al, ; Pantin‐Jackwood et al, ; Shibata, Okamatsu, et al, ; Tanikawa et al, ). However, recently, novel H7N9 and H7N2 reassortants of the zoonotic H7N9 AIVs have been detected in ducks in China (Shi et al, ). Phylogenetic analysis disclosed that these reassortants were generated by reassortment between the zoonotic H7N9 AIVs and unknown duck AIVs.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that (a) the patient had no history of avian exposure except to the ducks in his farm, (b) the samples from his or his neighbor's farm were H7‐positive by real‐time RT‐PCR, and (c) the genetic relatedness to duck viruses, the source of infection could be the virus circulated in the duck farms. HPAI H7 virus in ducks was also detected in Fujian in 2017 . It further supported that these HPAI H7N9 variants may generate in ducks.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, virus subtyping was usually delayed due to difficulties in recognizing novel serotype of influenza virus in clinic setting. Recent regular surveillance from Chinese Minister of Agriculture showed that H10N8 virus still existed in the poultry …”
Section: Introductionmentioning
confidence: 99%